An adaptive fuzzy sliding‐mode control for regenerative braking system of electric vehicles - Mei, Peng; Karimi, Hamid Reza; Yang, Shichun; Xu, Bin; Huang, Cong (International journal of adaptive control and signal processing, 2022)
Summary This article proposes a novel fuzzy sliding‐mode control scheme under an adaptive control strategy for energy management mechanism in electric vehicles that are subject to a regenerative braking system. The effectiveness of the fuzzy logic controller is to adjust the sliding mode parameters according to the slip ratio tracking error between the optimal slip ratio and the actual slip ratio. Specifically, the proposed torque distribution strategy can integrate the best battery condition and energy recovery efficiency under the practical constraints through this control method by fixing the pneumatic braking torque and motor torque. Finally, an electric vehicle model is established in the Simulink environment to verify the applicability of the proposed control algorithm.